Agent's mountain rescue - Bokal, Jennifer D. (Bokal, Jennifer D. Wyoming nights., 2020)
"Operative Liam Alexander is a tracker, used to working solo, even in treacherous mountain terrain. He only agrees to partner with child psychologist Holly Jacobs to stop a deadly serial killer. When Liam's daughter is abducted by the twisted murderer, what begins as a working relationship turns into so much more. But can Liam rescue his baby girl without sacrificing the family he's grown to love?" --Amazon.